2020
DOI: 10.3390/ijms21072371
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Renal Biomarkers of Kidney Allograft Fibrosis—A Study in Renal Transplant Patients

Abstract: Renal transplantation is the preferred treatment of end stage renal disease, but allograft survival is limited by the development of interstitial fibrosis and tubular atrophy in response to various stimuli. Much effort has been put into identifying new protein markers of fibrosis to support the diagnosis. In the present work, we performed an in-depth quantitative proteomics analysis of allograft biopsies from 31 prevalent renal transplant patients and correlated the quantified proteins with the volume fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…24 Quantitative proteomic studies of allograft biopsies have shown factor XIII A chain to correlate with degree of fibrosis. 25 Further evidence that donor macrophages contribute to pathology in ABMR is their differential expression of C1QA, C1QB, and C1QC. C1q-binding DSAs have been shown to confer a poor prognosis after ABMR.…”
Section: Discussionmentioning
confidence: 99%
“…24 Quantitative proteomic studies of allograft biopsies have shown factor XIII A chain to correlate with degree of fibrosis. 25 Further evidence that donor macrophages contribute to pathology in ABMR is their differential expression of C1QA, C1QB, and C1QC. C1q-binding DSAs have been shown to confer a poor prognosis after ABMR.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a comprehensive control network for the actin cytoskeleton including several subunits of the actin-related protein 2/3 complex was found uniquely expressed (upregulated) in patient samples with progressive injury and a high risk for graft loss [19]. A recent proteomic analysis of allograft biopsies from renal transplant patients supported these findings by demonstrating that increased expression of ARP2/3 subunit 2 correlated with kidney fibrosis [20]. We further confirm their observation adding a brand-new piece of information; however, we do not know how cytoskeleton modification in PBMC could be correlated with increased fibrosis in the graft.…”
Section: Discussionmentioning
confidence: 89%
“…We further confirm their observation adding a brand-new piece of information; however, we do not know how cytoskeleton modification in PBMC could be correlated with increased fibrosis in the graft. Indeed, these studies [19,20] employed a classical proteomic approach identifying the proteins up or downregulated at the graft tissue level, whereas we investigated circulating immune cells using what we may define a functional proteomic approach. More functional studies including the recruitment of these cells in the kidney and their role in inflammation and fibrosis in the graft should be performed to better clarify the role of PBMC's cytoskeleton modification in the pathogenesis of graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…ATA samples were prepared for proteomic analysis also as previously described [21]. In brief, sections were deparaffinized in chloroform, and proteins were extracted using 1 M DTT, 0.2 M TEAB and 10% sodium dodecyl sulphate, and incubated at 99 °C for 20 min, and then at 80 °C for 120 min.…”
Section: Preparation Of Samples For Proteomic Analysismentioning
confidence: 99%